2011
DOI: 10.1007/s00005-010-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Borreliosis: Indirect Immunofluorescence Assay, Enzyme-Linked Immunosorbent Assay and Immunoblotting

Abstract: Lyme disease is an infectious, multi-system, tick-borne disease caused by genospecies of Borrelia burgdorferi bacteria sensu lato, characterized by remarkable heterogeneity. In this situation choosing an optimal antigen array for diagnostic tests seems problematic. The serological tests for borrelia routinely done in laboratories often produce ambiguous results, which makes a proper diagnosis rather complicated and thus delays the implementation of an appropriate treatment regimen. Thirty-seven outpatients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The ELISA serologic method is recommended as a screening test in epidemiological studies (15). Reagent antigens used in the ELISA kit cannot be standardized so discrepancy may be found between the results obtained in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ELISA serologic method is recommended as a screening test in epidemiological studies (15). Reagent antigens used in the ELISA kit cannot be standardized so discrepancy may be found between the results obtained in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ELISA and WB kits used the antigen of the European strain. Studies indicate that if the immunoblotting assay includes OspC antigens to detect IgM and vlsE antigen to detect IgG, the specificity of the diagnostic test is increased (15,17). In our study, in the WB test, the number of OspC antigen bands (other bands: p39, vlsE) in IgMpositive patients and the number of vlsE antigen bands in IgG-positive patients was seen to be more positive (other bands: OspC, p39, p83, p58, p21, p20, p19, and p18).…”
Section: Discussionmentioning
confidence: 99%
“…The recommended two-tiered testing also misses as much as 44% of those with late Lyme disease. 24 Part of the difficulty in finding antibodies against Borrelia is that they can be bound in circulating immune complexes. These tests also do not detect other related Borrelia species that cause Lyme-like illness, such as Borrelia miyamotoi and Borrelia sensu lato .…”
Section: Background and Overviewmentioning
confidence: 99%
“…In patients with early phase LD, the most commonly detected antibodies are IgM against flagelin protein (p41) and outer surface protein C (OspC). Many studies have also been confirmed in Poland (4,15,16).…”
Section: S70mentioning
confidence: 79%